Badi in the poetry of Bashar ibn Bard - Younis, Wouda; Al-Shawash, Yasser (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Al-Budaiya is one of the most prominent monetary issues that occupied large areas in the monetary arena, especially in the second century AH. The term Al-Budaiya was associated with modern poets, headed by Bashar Ibn Bard Al-Aqili, He was able to devise a unique path for himself to become the sheikh of a new graphic school, followed by the approach of the subsequent poets and followed him.